The morphology of circulus arteriosus cerebri in the red squirrel (Sciurus vulgaris) - Aydin, A. (Czech Academy Agricultural Sciences, 2008)
In this study, the circulus arteriosus cerebri of the squirrel was investigated. Ten squirrel were used. Coloured latex was given from left ventriculi of the all squirrels. Circulus arteriosus cerebri was examined after the dissection was made. The basilar artery was formed by merge of the right and left vertebral artery. The caudal communicans artery which was caudal part of circulus arteriosus cerebri was formed by the basilar artery on sulcus pontocrurale. From caudal to cranial, the branches originated from the basilar artery and circulus arteriosus cerebri to cerebrum and cerebellum were as follows: the caudal cerebelli artery, rami ad pontem, the rostral cerebelli artery, the caudal choroidea artery, the caudal cerebral artery, the internal ophtalmic artery, the rostral choroidea artery, the media cerebral artery, rami striati and the rostral cerebral artery. In squirrels a variability was observed in the branches that the rostral cerebral artery gives, and their endings. It was determined that the internal carotid artery didn't exist in 4 animals when the right and left vertebral artery were ligatured. It was found that the internal carotid artery didn't contribute to the arterial blood to circulus arteriosus cerebri and the arterial blood to circulus arteriosus cerebri of squirrels is provided via only the basilar artery.
Keywords: circulus arteriosus cerebri; brain; red squirrel (Sciurus vulgaris)